Investigation of crosslink structure of natural rubber during vulcanization using X-ray absorption near edge spectroscopy - Boonkerd, K; Limphirat, W (Journal of Metals, Materials and Minerals, 2020)
The X-ray absorption near edge spectroscopy technique (XANES) has been applied to determine the crosslinking structure of natural rubber (NR) during sulfur vulcanization process. The NR samples were prepared using DCBS as an accelerator at different sulfur to DCBS ratios (from 0.26 to 6.67). The results showed that with increasing cure time from tc50 to tc70, tc90 and tc100 the position of sulfur peak shifted to higher energy. This implied that the amount of polysulfidic crosslink gradually decreased with increasing cure time. This result supported the crosslinking mechanism proposed in the literature at which the polysulfidic crosslink is dominating at initial curing stage. Moreover, when rubber was over-cured for 20 min, the amount of polysulfidic crosslink further decreased indicating by shifting of sulfur peak to high energy. The effect of sulfur to accelerator ratio on the crosslink structure was also elucidated by XANES. The results showed that the position of sulfur peak passed through the lowest energy with the increasing of the sulfur to DCBS ratios. It means that the amount of polysulfidic crosslink was not simply correlated with the sulfur to accelerator ratios. It passed through maximum with increasing sulfur to accelerator ratio. This caused the reversion resistance of rubber no longer directly proportional to the sulfur to accelerator ratio. The result from this study indicated that XANES technique is a prospective tool to investigate the crosslink structure of sulfur cured rubber.